2003
DOI: 10.1542/peds.112.4.e298
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Bacillus Calmette-Guérin Scar Formation and Tuberculin Skin Test Reactivity in Infants in Lima, Peru

Abstract: ABSTRACT. Objectives. To determine the sensitivity of the bacillus Calmette-Guérin (BCG) scar as an indicator of previous vaccination and to ascertain the tuberculin skin test (TST) response in infancy after vaccination in a community from an area hyperendemic for tuberculosis (TB).Methods. In a birth cohort of healthy term infants from Lima, Peru, a single dose of BCG vaccine was administered within the first month of life. Scar formation was assessed biweekly during the first 6 months and again at 3 years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…The community prevalence of TST positivity is an important indicator of TB control because it is not confounded by changes in TB case finding that can considerably increase or decrease estimates of the incidence of TB disease. 5 In TBendemic countries such as Peru, the TST is the only widely used method for diagnosing latent infection, especially in children [7][8][9][10] despite difficulty interpreting results in subjects who have received the Bacille Calmette-Guérin (BCG) vaccine. The great majority of children in Peru receive the BCG vaccine at birth.…”
Section: Introductionmentioning
confidence: 99%
“…The community prevalence of TST positivity is an important indicator of TB control because it is not confounded by changes in TB case finding that can considerably increase or decrease estimates of the incidence of TB disease. 5 In TBendemic countries such as Peru, the TST is the only widely used method for diagnosing latent infection, especially in children [7][8][9][10] despite difficulty interpreting results in subjects who have received the Bacille Calmette-Guérin (BCG) vaccine. The great majority of children in Peru receive the BCG vaccine at birth.…”
Section: Introductionmentioning
confidence: 99%
“…A "visible scar" was defined as a scar measuring 2 or more millimeters. Scar failure rate was 1.4% (23).…”
Section: Discussionmentioning
confidence: 91%
“…12 The authors reported that scars do not form when immune system of the infants is not fully mature, and in cases of vaccination performed using an improper technique or an impotent vaccine. 13 At least one BCG scar was present in our entire patient group, and none of our patients was immunosuppressed. A positive correlation was found between age and horizontal and vertical diameter of BCG scars in this study.…”
mentioning
confidence: 71%